2013
DOI: 10.1037/a0032581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tier 3 intervention for students with persistent reading difficulties and characteristics of inadequate responders.

Abstract: This article describes a randomized controlled trial conducted to evaluate the effects of an intensive, individualized, Tier 3 reading intervention for second grade students who had previously experienced inadequate response to quality first grade classroom reading instruction (Tier 1) and supplemental small-group intervention (Tier 2). Also evaluated were cognitive characteristics of students with inadequate response to intensive Tier 3 intervention. Students were randomized to receive the research interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
82
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 57 publications
(76 reference statements)
18
82
0
1
Order By: Relevance
“…These fi ndings further support previous work by Fletcher et al ( 2011 ) and Denton et al ( 2012 ) on the role of both linguistic and cognitive factors not just in word reading but also in word reading development. It seems that in Hebrew similar basic abilities are needed in order to improve reading abilities.…”
Section: Phonological Awareness As the Driving Force Of Rtisupporting
confidence: 91%
See 1 more Smart Citation
“…These fi ndings further support previous work by Fletcher et al ( 2011 ) and Denton et al ( 2012 ) on the role of both linguistic and cognitive factors not just in word reading but also in word reading development. It seems that in Hebrew similar basic abilities are needed in order to improve reading abilities.…”
Section: Phonological Awareness As the Driving Force Of Rtisupporting
confidence: 91%
“…These studies identifi ed diffi culties with phonological awareness, rapid naming, vocabulary, and oral language skills, as the most consistent cognitive attributes of inadequate responders. In addition, Denton et al ( 2012 ) reported that measures of phonological awareness and language processing characterized children who did not benefi t from 2 years of intervention. Fletcher et al ( 2011 ) evaluated the cognitive attributes of fi rst grade students who responded adequately and inadequately to a Tier 2 reading intervention.…”
Section: The Cognitive Profi Le Of Children Who Benefi T From Intervementioning
confidence: 97%
“…As many as nine experimental or quasi-experimental RTI implementation studies have included Tier 3 intervention (Authors, in press; Beach & O'Connor, 2013; Denton, Fletcher, Anthony & Francis 2006; Denton, Tolar, Fletcher, Barth, Vaughn & Francis, 2013; Gilbert et al, 2013; O'Connor, Harty, & Fulmer, 2005; Vaughn, Wanzek, Linan-Thompson & Murray, 2007; Vaughn, Wanzek, Murray, Scammacca, Linan-Thompson, & Woodruff, 2009; Vellutino, Scanlon, Zhang & Schatschneider, 2008). Notably, these studies consistently included at least three of the five core components deemed essential for RTI implementation according to Gersten et al's (2009) Practice Guide for Response to Intervention (universal screening, progress monitoring, increasingly intensive tiers of intervention, and fidelity of implementation).…”
Section: Longitudinal Multi-tier Rti Researchmentioning
confidence: 99%
“…Denton and colleagues conducted two studies examining the effect of Tier 3 for primary grade students who had demonstrated inadequate response to well-implemented Tier 1 and Tier 2 in first grade (Denton, Fletcher, Anthony, & Francis, 2006; Denton et al, 2013). In the first study, Denton and colleagues located students who had not responded to an earlier first grade intervention (Mathes et al, 2005) and added additional students who were in second and third grade with similar reading scores; a total of 27 inadequate responders received intensive Tier 3 intervention (half had participated in the prior study and received Tier 1 or Tier 2 but half had not).…”
Section: Longitudinal Multi-tier Rti Researchmentioning
confidence: 99%
“…Seules quelques études ont évalué l'effet du palier III à l'intérieur d'une même année scolaire, consécutivement aux paliers I et II (Al Otaiba et al, 2014;Fien, Smith, Smolkowski, Baker, Nelson, et Chaparro, 2015;Gilbert, Compton, Fuchs, Fuchs, Bouton, Barquero et Cho, 2013), et elles concernent typiquement les élèves de la maternelle à la 2 e année du primaire Toste, Compton, Fuchs, Fuchs, Gilbert, Cho, Barquero et Bouton, 2014). Les autres études ont surtout évalué l'effet du palier III après une année d'intervention aux paliers I et II (Denton et al, 2013). C'est dire que, dans l'état actuel des connaissances scientifiques, plusieurs questions restent encore ouvertes quant aux modalités optimales de chaque palier.…”
Section: Le Concept De Palier D'interventionunclassified